Outcomes after multiple courses of granulocyte colony‐stimulating factor and growth hormone in decompensated cirrhosis: A randomized trial. Issue 4 (25th July 2018) - Verma, Nipun; Kaur, Amritjyot; Sharma, Ratiram; Bhalla, Ashish; Sharma, Navneet; De, Arka; Singh, Virendra
Abstract : Decompensated cirrhosis (DC) carries a high mortality. Liver transplantation (LT) is the treatment of choice; however, the limited availability of donor organs has resulted in high waitlist mortality. The present study investigated the impact of multiple courses of granulocyte‐colony stimulating factor (G‐CSF) with or without growth hormone (GH) in these patients. Sixty‐five patients with DC were randomized to standard medical therapy (SMT) plus G‐CSF 3 monthly plus GH daily (group A; n = 23) or SMT plus G‐CSF (group B; n = 21) or SMT alone (group C; n = 21). The primary outcome was transplant‐free survival (TFS) at 12 months. Secondary outcomes were mobilization of CD34 + cells at day 6 and improvement in clinical scores, liver stiffness, nutrition, episodes of infection, and quality of life (QOL) at 12 months. There was significantly better 12‐month TFS in groups A and B than in group C ( P = 0.001). At day 6 of therapy, CD34 + cells increased in groups A and B compared to baseline ( P < 0.001). There was a significant decrease in clinical scores, improvement in nutrition, better control of ascites, reduction in liver stiffness, lesser infection episodes, and improvement in QOL scores in groups A and B at 12 months as compared to baseline ( P < 0.05). The therapies were well tolerated. Conclusion : Multiple courses of G‐CSF improved 12‐month TFS, mobilized hematopoietic stem cells, improved disease severity scores, nutrition, fibrosis, QOL scores, ascites control, reduced infections, and the need for LT in patients with DC. However, the use of GH was not found to have any additional benefit. (Hepatology 2017).